2016
DOI: 10.1002/alr.21798
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cysteinyl leukotriene receptor 1 and 2 (CysLTR1 and CysLTR2) in the lymphocytes of hyperplastic tonsils: comparison between allergic and nonallergic snoring children

Abstract: The expression of CysLTR is higher in the lymphocytes of the NS children, and CysLTR2 shows greater expression than CysLTR1 Respiratory allergies do not appear to be a stimulus for AH occurrence. Newer drugs capable of blocking both CysLTRs warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The initial open-labeled study examining a potential role for anti-leukotriene therapy in pediatric OSA showed encouraging evidence that improvements in both the severity of respiratory disturbance and in the adenoid size could be anticipated in a large proportion of children with mild OSA [60]. We subsequently identified the presence of increased expression and activity of cysteinyl leukotriene receptors within lymphadenoid tissues of OSA children, and these could even be detected in exhaled condensate, serum, circulating white blood cells, or in urine [61][62][63][64][65][66][67][68][69][70]. Two RCTs have been conducted to date and have shown the favorable response to montelukast as a single agent in the treatment of pediatric OSA [71,72].…”
Section: Montelukastmentioning
confidence: 99%
“…The initial open-labeled study examining a potential role for anti-leukotriene therapy in pediatric OSA showed encouraging evidence that improvements in both the severity of respiratory disturbance and in the adenoid size could be anticipated in a large proportion of children with mild OSA [60]. We subsequently identified the presence of increased expression and activity of cysteinyl leukotriene receptors within lymphadenoid tissues of OSA children, and these could even be detected in exhaled condensate, serum, circulating white blood cells, or in urine [61][62][63][64][65][66][67][68][69][70]. Two RCTs have been conducted to date and have shown the favorable response to montelukast as a single agent in the treatment of pediatric OSA [71,72].…”
Section: Montelukastmentioning
confidence: 99%
“…They are also systemically and locally involved in the process of inflammation in AH [11] . Studies have confirmed the overexpression of CysLTR1 [12] and CysLTR2 [13] in the adenoid tissue. Also, treatment with leukotriene receptor antagonist has been shown to reduce the adenoid volume [14] .…”
Section: Discussionmentioning
confidence: 72%
“…Those data suggest that the activation of p-ERK1/2 is involved in the progression of adenoid hypertrophy. It has been reported that the biological functions of CYSLTR1 in allergic responses is closely related to the activation of ERK1/2 signaling pathway (16). In the present study, HAECs with CYSLTR1 overexpression and knockdown were constructed to investigate the interactions between CYSLTR1 and ERK1/2.…”
Section: Discussionmentioning
confidence: 95%